Improving the Quality and Safety Standard in Implementing E-Arbitration in Resolving Islamic Banking Disputes in Malaysia - Mohammad Azam Hussain; Mohamad Fateh Labanieh; Nazli Mahdzir (International Journal of Supply Chain Management, 2020)
Electronic arbitration (hereinafter referred to as e-arbitration) is a combination of law and technology. Even though e-arbitration has not been implemented yet in Malaysia, the Malaysian authorities should be ready to meet the non-legal requirements for implementing it in the future as compliment to the existing traditional arbitration method. By using legal research methodology, this article endeavours to examine how the future implementation of e-arbitration in resolving the Islamic banking dispute can be improved especially in handling cyber security. The collected data is analytically and critically scrutinised using content analysis method. The article found that enhancing cyber security is a pressing need to improve the future implementation of e-arbitration in Malaysia successfully. Therefore, the article recommended several legal and technical measures to enhance cyber-security in e-arbitration in Malaysia.